Developing and implementing an instrument for assessing critical thinking and visual representations in learning Physics materials of Optical Instruments - Nurulhasni, Dewi; Nurbaiti, Eka Ayu; Nabila, Rosa Safirotun; Jumadi, Jumadi (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
This study aims to develop an assessment instrument to measure students' critical thinking and visual representation abilities in optical instrument material. This research and development (R&D) employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional model. This research develops a test instrument that has more specific stages so the ADDIE development stage is integrated with the development stage of the test instrument developed by Mardapi. The subjects in this study are grade XI students of State Madrasah Aliyah (MAN) 4 Bantul. This study produced a test instrument for measuring students' critical thinking and visual representation abilities, with high validity,and analyzed using Aiken's V. The items for assessing critical thinking and visual representation abilities were analyzed using the QUEST program with the following findings. (1) The analysis results of instrument validation using Aiken's V obtained an average Aiken's Value above 0.4 with high validity and moderate validity criteria so all items are valid. (2) The pre-test analysis on item estimates obtained MNSQ Infit in the range 0.77-1.30 and the value of outfit t â‰¤ 2 and in the MNSQ Infit case estimates in the range 0.77-1.30, so overall, the items matched to Rasch models. (3) Post-test analysis on item estimates obtained MNSQ Infit in the range 0.77-1.30 and outfit t value â‰¤ 2 and in case estimates MNSQ Infit in the range 0.77-1.30 so, overall, items are in accordance with Rasch models. (4) The reliability of the pre-test items is 0.92 while the reliability of the post-test items is 0.76. (5) The difficulty level of the items in the pre-test results shows that Question 10 is the most difficult while number 3 is the easiest, and in the post-test results, Question 8 is the most difficult while Question 6 is the easiest.